Probing the dominant lived-experiences of married college students valuing the resiliency theory - Cambri, Beverly Gay N. (Linguistics and Culture Review, 2021)
Life for married college students can indeed be very tedious and challenging. But with perseverance, good support system, and proper motivation these students will be able to cope well with the issues they face at present. This study elucidates the dominant lived-experiences of married college students valuing the resiliency theory. Qualitative study was employed, back up with triangulation to substantiate the theory used in the study. The study is deemed to denude the lived-experiences of married students while they are studying in a private or public universities in Region 02. To assess resiliency, the tool Cannor- Davidson Resilience Scale was also made use to measure the strength of these students while taking a risk in their lives. In this study, it revealed that married students are even stronger while they are facing tribulations in their respective lives. They even gamble their future but still optimistic enough to face whatever future may give them. Married students were able to exhibit compassion and empathy, resourceful and flexible and they show concern to everyone. One great thing that had been uncovered was that married students were problem solvers and critical thinkers.